Security Rights in Intellectual Property in Finland - Juutilainen Teemu (Springer, 2022)
Finnish law provides for the registrable pledges of patents, trademarks and other registrable intellectual property rights. This part of the legal framework is, by and large, adequate, so that one can reliably obtain fully effective security rights over these types of intellectual property rights. However, statistical data from the Finnish Patent and Registration Office shows that this opportunity is quite rarely used. In turn, copyright and other intellectual property rights that are not registrable under Finnish law are problematic in terms of achieving third-party effectiveness. Solutions proposed in legal literature, such as accepting security transfers of copyright as effective against third parties without any form of publicity, remain disputed and uncertain. Indeed, the most common way of using intellectual property rights as security under Finnish law is through the enterprise mortgage. Enterprise mortgages are frequently used (although often as a supplementary security, due to their limited priority) and they cover all types of intellectual property rights.
Security Rights in Intellectual Property